Prevalence of Neuropathic Pain in Morocco: A Systematic Review and Meta-Analysis - Zhor Zeghari; Jihane Belayachi; Redouan El Ouardi; Redouane Abouqal (Life)
This study aims to assess the prevalence of neuropathic pain in the Moroccan population through a systematic review and meta-analysis using a generalized linear mixed model (GLMM). The PRISMA guidelines for systematic reviews and meta-analysis were followed. All observational prevalence studies, conducted in both the general population and hospital settings in Morocco, published before 1 December 2023, were included, provided that neuropathic pain was identified based on consensus criteria. The databases searched included PubMed, Scopus, Web of Science, and the gray literature (Google Scholar). Data on the sample size, subgroups, sociodemographic and clinical characteristics of participants, as well as the methodology of each study, were extracted. The Joanna Briggs Institute tool for prevalence studies was used to assess the risk of bias. A random-effects generalized linear mixed model was applied for direct data adjustment, using Knapp–Hartung standard error correction. Heterogeneity was explored using Cochran’s Q test, Higgins’ I2 statistic, and prediction intervals. Subgroup analysis was performed based on underlying pathology, while meta-regression was conducted according to age and sex ratio. Publication bias was assessed using the Doi plot and LFK test. Sensitivity analysis was performed by stratifying studies based on their risk of bias. The statistical analysis was conducted using R software version 4.3.1 with the meta, metafor, metasens, and robvis packages. A total of 33 publications were identified, of which 17 studies were retained after removing duplicates and applying the eligibility criteria. These studies were published between 2013 and 2023 and included either the general population (one study) or patients with diabetes (seven), obesity (one), rheumatologic conditions (six), Parkinson’s disease (one), or cancer (one). The DN4 score was the most commonly used tool to diagnose neuropathic pain. The risk of bias was rated as low in two studies, moderate in eight, and high in seven. The pooled overall prevalence was 22% (95% CI [14.8; 31.5]) with an I2 of 98% (p < 0.01). In subgroup analyses, the prevalence was 19.9% among rheumatology patients, 10.2% in oncology patients, 9.4% in Parkinson’s patients, 26.6% in diabetics, 58.6% in obese individuals, and 10.6% in the general population. Meta-regression by sex indicated significantly lower prevalence in men, and prevalence increased with age but did not reach statistical significance. After stratification based on the risk of bias, the pooled prevalence was 15.4% for the two studies with a low risk of bias. The overall prevalence of neuropathic pain in Morocco is relatively high at 22%, with significant variability across medical specialties. However, this prevalence is likely overestimated. Stronger and higher-quality studies are needed to obtain more accurate estimates.